2016
DOI: 10.1002/2016gl069428
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variations in fault friction related to lithology from rupture and afterslip of the 2014 South Napa, California, earthquake

Abstract: Following earthquakes, faults are often observed to continue slipping aseismically. It has been proposed that this afterslip occurs on parts of the fault with rate‐strengthening friction that are stressed by the main shock, but our understanding has been limited by a lack of immediate, high‐resolution observations. Here we show that the behavior of afterslip following the 2014 South Napa earthquake in California varied over distances of only a few kilometers. This variability cannot be explained by coseismic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
96
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(110 citation statements)
references
References 30 publications
13
96
1
Order By: Relevance
“…4) ( 38 , 41 , 45 ). The hand measurements made at the day of the event ( 34 , 44 ) document a peak in coseismic surface offset in the northern portion of the rupture and a deficit in the south (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4) ( 38 , 41 , 45 ). The hand measurements made at the day of the event ( 34 , 44 ) document a peak in coseismic surface offset in the northern portion of the rupture and a deficit in the south (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…At three South Napa afterslip sites, the rupture propagated upward through 0-3-km-thick basin deposits (Brooks et al, 2015;Floyd et al, 2016); whereas only at the NLOD site was the rupture in bedrock near the surface. However, on the creeping Superstition Hills fault (Wei et al, 2009) after the 1987 M 6.6 earthquake, at the mostly ∼2-3-km-deep basin sites (Williams and Magistrale, 1989), AFTER solutions indicated that most significant afterslip (∼95%) would occur within only 2 yrs .…”
Section: Global Variation In Afterslip Duration and Implications For mentioning
confidence: 97%
“…The former, composed of three repeating events (in 1995, 2000, and 2005), is located on the Browns Valley segment of the fault, ∼ 4 km NW of the northern end of the 2014 earthquake rupture zone (e.g., Floyd et al, 2016) and at 6-km depth. The former, composed of three repeating events (in 1995, 2000, and 2005), is located on the Browns Valley segment of the fault, ∼ 4 km NW of the northern end of the 2014 earthquake rupture zone (e.g., Floyd et al, 2016) and at 6-km depth.…”
Section: How the Repeating Earthquakes Are Distributedmentioning
confidence: 99%